Roger Welles papers - Welles, Roger, 1862-1932.; Welles, Harriet Ogden Deen.
Correspondence, journals, article and speech file, orders to duty, newspaper clippings, printed matter, photographs, and other papers relating to Welles's service as director of the U.S. Office of Naval Intelligence; commander of the U.S. Navy Asiatic Fleet, U.S. Navy Atlantic Fleet, and U.S. Naval Forces, Europe; and special representative for the World's Columbian Exposition in Chicago, Ill., 1893. Subjects include exploration of the Orinoco River (Colombia and Venezula), the Indians of Venezuela, Spanish-American War (1898), European political affairs of the 1920s, a general strike in Great Britain, and the rise of fascism in Italy. Includes correspondence with Welles's mother, Mercy D.A. Welles, and other family members and a 1910 diary of Welles's wife, Harriet Ogden Deen Welles. Correspondents include James Nicholls Allison, Philip Andrews, Victor Blue, the marquis de Balincourt, Mark L. Bristol, William I. Buchanan, Robert E. Coontz, William Eleroy Curtis, Josephus Daniels, Arthur Philip Fairfield, Ogden H. Hammond, Eugene F. McDonald, Alexander Pollock Moore, Albert P. Niblack, William Lindsay Scruggs, Joseph W. Sefton, Charles West Stewart, C. Symon, and Ovington Eugene Weller.
Naval officer.
Collection material in English, with French.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: Allison, James Nicholls, -- 1848-1918 -- Correspondence; Andrews, Philip, -- 1866-1945 -- Correspondence; Balincourt, -- marquis de -- Correspondence; Blue, Victor, -- 1865-1928 -- Correspondence; Bristol, Mark L. -- 1868-1939 -- Correspondence; Buchanan, William I. -- 1852-1909 -- Correspondence; Coontz, Robert E. -- 1864-1935 -- Correspondence; Curtis, William Eleroy, -- 1850-1911 -- Correspondence; Daniels, Josephus, -- 1862-1948 -- Correspondence; Fairfield, Arthur Philip, -- 1877-1946 -- Correspondence; Hammond, Ogden H. -- 1869-1956 -- Correspondence; McDonald, Eugene F., -- 1886- -- Correspondence; Moore, Alexander Pollock, -- 1867-1930 -- Correspondence; Niblack, Albert P. -- 1859-1929 -- Correspondence; Scruggs, William Lindsay, -- 1836-1912 -- Correspondence; Sefton, Joseph W., -- 1882-1966 -- Correspondence; Stewart, Charles West, -- 1859-1929 -- Correspondence; Symon, C. -- Correspondence; Weller, Ovington Eugene, -- 1862-1947 -- Correspondence; Welles, Mercy D. A. -- 1832-1922 -- Correspondence; Welles family -- Correspondence; United States. -- Naval Forces, Europe; United States. -- Navy -- Intelligence specialists; United States. -- Navy. -- Asiatic Fleet; United States. -- Navy. -- Atlantic Fleet; United States. -- Office of Naval Intelligence; Exhibitions -- Illinois -- Chicago; Fascism -- Italy; Indians of South America -- Venezuela; Military intelligence; Spanish-American War, 1898.; Strikes and lockouts -- Great Britain; Colombia -- Discovery and exploration; Europe -- Politics and government -- 1918-1945; Orinoco River (Venezuela and Colombia) -- Discovery and exploration; Venezuela -- Discovery and exploration; Naval officers